Respuesta :

Answer:

x = -2 and y = 3

Step-by-step explanation:

It is given that,

4x + 5y = 7  ----(1)

3x – 2y = –12    ---(2)

To find the value of x and y

eq(1) * 3 ⇒

12x + 15y = 21   ----(3)

eq(2) * 4 ⇒

12x - 8y = -48  ---(4)

eq(3) - eq(4) ⇒

12x + 15y = 21   ----(3)

12x - 8y = -48  ---(4)

0 + 23y = 69

y = 69/23 = 3

y = 3

Substitute the value of y in eq(1)

4x + 5y = 7    ----(1)

4x + 5*3 = 7

4x = 7 - 15 = -8

x = -8/4 = -2

Therefore x = -2 and y = 3

ANSWER

x=-2,y=3

EXPLANATION

The system of equations is:

[tex]4x + 5y = 7...(1)[/tex]

and

[tex]3x - 2y = - 12...(2)[/tex]

We multiply the first equation by 2.5 to get:

[tex]7.5x - 5y = - 30...(3)[/tex]

We add equations (1) and (3)

[tex]4x+7.5x=-30+7[/tex]

[tex]11.5x = - 23[/tex]

Divide both sides by 11.5

[tex]x = - \frac{23}{11.5} [/tex]

[tex]x = - 2[/tex]

Put x=-2 into the first equation or any other equation and solve for y.

[tex]4( - 2) + 5y = 7[/tex]

[tex] - 8 + 5y = 7[/tex]

[tex]5y = 7 + 8[/tex]

[tex]5y = 15[/tex]

[tex]y = 3[/tex]